2006
DOI: 10.1002/micr.20277
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical reconstruction of brachial artery injuries in displaced supracondylar fracture humerus in children

Abstract: Between March 2000 and March 2005, 840 children with grade III supracondylar humeral fractures presented for treatment, consecutively at our hospital. One hundred twenty had absent or diminished (detected by Doppler but not palpable) radial pulse on initial examination. Eighty-nine of these 120 children recovered pulse (palpable) after closed reduction and percutaneous pinning of the fracture. The remaining 31 children had persistent absent radial pulse. Twenty-two of the 31 children had median nerve signs. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
0
41
0
1
Order By: Relevance
“…They are usually reported in cases of proximal and supracondylar humeral fractures. 5,6 Uncomplicated humeral shaft fractures are usually treated conservatively. The usual operative methods used are the dynamic compression plate (DCP) and intramedullary nail.…”
mentioning
confidence: 99%
“…They are usually reported in cases of proximal and supracondylar humeral fractures. 5,6 Uncomplicated humeral shaft fractures are usually treated conservatively. The usual operative methods used are the dynamic compression plate (DCP) and intramedullary nail.…”
mentioning
confidence: 99%
“…CCDS correctly identified arterial lesions and normal patency of the brachial artery was restored. Along with others, 4,12,14,17,26 we emphasise that in those cases, a satisfactory temporary collateral circulation could not have guaranteed a good long-term outcome. Cold intolerance, sometimes with Raynaud's phenomenon, dysaesthesia, claudication of the forearm, delayed development and growth arrest of the involved limb and complete loss of function have been reported following arterial damage associated with a supracondylar fracture.…”
Section: Discussionmentioning
confidence: 65%
“…Cold intolerance, sometimes with Raynaud's phenomenon, dysaesthesia, claudication of the forearm, delayed development and growth arrest of the involved limb and complete loss of function have been reported following arterial damage associated with a supracondylar fracture. 4,7,9,12,17 In Blakey et al's 4 series of 26 patients with a pink pulseless hand after reduction of the fracture with a mean follow-up of 15.5 years, only four had undergone an exploration, three immediately, when an arterial repair was possible and one 48 hours after the injury, which was unsuccessful. Thus, 23 patients developed an ischaemic contracture of the forearm and hand and they concluded that a pink pulseless limb is ischaemic and recommended urgent exploration under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supracondylar fracture of the humerus in children is one of the most common fractures seen in orthopaedic outpatient department all over the world accounting for 60% of all elbow fracture in children in the first decade of life [1]. Traditionally this type of fracture is associated with high rate of malunion, nerve injuy, and vascular complications [2].…”
Section: Discussionmentioning
confidence: 99%